Auto-update container lids scanner with expiration date display / Siti Zakirah Zulkepli … [et al.] - Zulkepli, Siti Zakirah; Mohamad Rodzi, Nurdalila Farhana; Senin, Nur Sahirah; Abd Manan, Nurul Sharina; Meng Hee, Rosyanieza; Mohamad Derapi, Asya Qasreena; Osman, Idris (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
This paper introduces a ground-breaking solution aimed at addressing the pressing issue of food safety: The Auto-Update Container Lids Scanner with Expiration Date Display. In response to the inadequacies of current methods for monitoring food freshness. By offering users a simple and intuitive means of tracking the freshness of their stored provisions, this product allows for the setting of personalized expiration dates and provides a dynamic real time countdown feature. As the expiration date approaches, the lid undergoes a visible colour shift, effectively signalling the progression toward expiration. Through this innovative technology, significant reductions in the risks associated with foodborne illness and waste are anticipated, thereby fostering improved food safety practices. Available in three sizes (small, medium, and large), the Auto-Update Container Lids Scanner cater to a wide range of food storage needs, accommodating items such as packaged food, and canned goods. Targeting busy parents, working adults, and upper-class status, this innovation seeks to streamline the process of food storage and consumption. This product incorporates scanner and barcode scanning capabilities, enabling automatic updates of expiration dates on both mobile devices and containers. This functionality not only enhances user convenience but also ensures precise monitoring of food freshness levels. For commercialization strategy, forging strategic partnerships with established food storage container manufacturers is recommended. Additionally, marketing campaigns focused on waste reduction and enhanced food safety could further bolster market penetration. The Auto-Update Container Lids Scanner have the potential to revolutionize how we store food, making them essential for modern consumers who prioritize food safety and freshness.